SISTEM PAKAR DIAGNOSA PENYAKIT MATA PADA MANUSIA DENGAN METODE FUZZY LOGIC (Information Technology and Telematics, 2016)
Abstract Expert system diagnosis of eye diseases in humans is an expert system that is able to identify the type of disease from the physical symptoms caused. The realization of this is the development of expert systems are capable of making web penyakuit diagnose human eye. Because if the diagnosis is done manually, it will often misdiagnosed eye disease in humans, sehinggan handling the disease becomes obstructed. The resulting Web expert system is able to diagnose the type of eye disease in humans by observing the symptoms caused by the patient. In conducting this analysis expert system, the authors use the method of Fuzzy Logic, whereas receipts to perform system design prototyping methods. Meanwhile, to make the development process, the writer uses analytical methods abbot. Analysis abbot is a way (method) to abstract objects (object) or so-called object-oriented systems analysis. Recently in doing the design of object-oriented systems, the authors use design tools such as UML diagram consisting of a class diagram, usecase diagrams and sequence diagrams. From analysis and design that, there is an expert system for the diagnosis of eye diseases in humans, so it can help clinicians and patients with diseases that arise. Abstrak Sistem pakar diagnosa penyakit mata pada manusia adalah suatu sistem pakar yang mampu mengidentifikasi jenis penyakit dari gejala-gejala fisik yang ditimbulkan. Wujud dari pengembangan sistem pakar ini adalah ini adalah pembuatan web yang mampu mendiagnosa penyakuit mata pada manusia. Karena jika diagnosa dilakukan secara manual, maka akan sering terjadi salah diagnosa penyakit mata pada manusia, sehinggan penanganan penyakit tersebut pun menjadi terhambat. Web sistem pakar yang dihasilkan mampu mendiagnosa jenis penyakit mata pada manusia dengan memperhatikan gejala-gejala yang ditimbulkan oleh pasien. Dalam melakukan analisa sistem pakar ini, penulis menggunakan metode Fuzzy Logic, sedangkan untuk melakukan perancangan sistem meggunakan metode prototyping. Sedangkan untuk melakukan proses pengembangan, penulis menggunakan metode analisa abbot. Analisa abbot adalah suatu cara (metode) untuk mengabstraksikan benda (objek) atau biasa disebut analisis sistem berorientasi objek. Terakhir dalam melakukan perancangan sistem berorientasi objek, penulis menggunakan  alat bantu perancangan berupa diagram UML yang terdiri dari diagram class, diagram usecase dan diagram sequence. Dari analisa dan perancangan tersebut, dihasilkan sebuah sistem pakar untuk mendiagnosa  penyakit mata pada manusia, sehingga dapat membantu dokter dan pasien dalam menangani penyakit yang timbul. Kata Kunci Sistem Pakar, Penyakit Mata, Fuzzy Logic